Approaches to participation in rural development - Oakley, Peter; Marsden, David; United Nations ACC Task Force on Rural Development (Geneva : Published on behalf of the ACC Task Force on Rural Development [by the] International Labour Office, 1984)
This present study represents an important element of the work programme of the panel. It further comprises of conceptual, analytical work; exchange of experience among developing countries in participatory initiatives at the grass-roots level.
Includes bibliographies.
ahz 12/03/2019
Loans
Keywords: Rural development